Current capabilities of thyroid cancer diagnosis (literature review) - E. E. Bober; I, G, Frolova; E. L. Choinzonov; S. A. Velichko; N. Yu. Bystrova; M. R. Mukhamedov (Сибирский онкологический журнал)
The review deals with the problem of comprehensive diagnostic capabilities for thyroid cancer. In spite of the multiple studies, the question on the role of magnetic-resonance imaging in diagnostic algorithms for thyroid cancer remains disputable